Negara Sebagai Mediator Tumbuh Kembangnya Ekonomi Berbasis Syariah: Perspektif Filsafat - Rakhmawan Suherli, Ian; Nurrohman, Nurrohman; Abdul Malik, Zaini; Mutaqin, Kikin (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
Islamic economics is an economic system that is a minority used in the world compared to other economic systems. Islam is a comprehensive religion and governs all aspects of life including economics. Islamic economics aims to create economic schemes that refer to Islamic principles, such as social justice, balance, avoiding usury, and sustainable growth. The economic sources of sharia come from the Quran, as Sunnah or al Hadith, the history of Islamic society, and empirical data. The state has an important role in supporting and regulating Islamic economic practices through appropriate regulations and policies. The state and the Islamic economy have the same interest in creating social justice, economic stability, and public welfare. The relationship between religion and state also affects the development of a country's sharia economy. In Indonesia, the government has supported the implementation of the sharia economy through various regulations and policies such as the Sharia Banking Law. With the right support from the state, the Islamic economy is expected to develop faster and provide benefits to the community.